IMPLEMENTASI SISTEM INFORMASI PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (Studi Kasus di SMAN 1 Binamu Jeneponto) - kasmawati, Kasmawati (Inspiratif Pendidikan, 2017)
Abstract: The quality of information greatly affects the performance and results of work of education managers and for educational participants. Although SMAN1 jeneponto has provided academic-based academic information services, but the way data management is not effective when a fast information is required with certain criteria. The existence of a fragmented data management system requires a control system to control all existing information systems according to the desired flow. So that the system must be combined into a single data processing system that can provide information at any time needed, of course by people who are eligible to use the system. In a learning process is still commonly found in the use of computers has not been maximized but in SMAN1 Jeneponto actually have long use ICT in the learning process of PAI. Improving the quality of education is one of the most important elements in efforts to improve the quality of human resources. In line with that, it is very important to note is the use of ICT in learning Islamic religious education. Common problem often faced by learners is still a lot of teachers who have not mastered the use of ICT so that learners is very difficult to obtain a satisfactory learning achievement because teachers not maximal on the use of ICT in teaching and learning process is good and correct in SMAN1 jeneponto